Assessment of antigenic difference of equine influenza virus strains by challenge study in horses. Issue 6 (9th August 2016) - Yamanaka, Takashi; Nemoto, Manabu; Bannai, Hiroshi; Tsujimura, Koji; Kondo, Takashi; Matsumura, Tomio; Gildea, Sarah; Cullinane, Ann
Abstract : We previously reported that horse antiserum against the Japanese equine influenza vaccine virus, A/equine/La Plata/1993 (LP93) exhibited reduced cross‐neutralization against some Florida sublineage Clade (Fc) 2 viruses, for example, A/equine/Carlow/2011 (CL11). As a result, Japanese vaccine manufacturers will replace LP93 with A/equine/Yokohama/aq13/2010 (Y10, Fc2). To assess the benefit of updating the vaccine, five horses vaccinated with inactivated Y10 vaccine and five vaccinated with inactivated LP93 were challenged by exposure to a nebulized aerosol of CL11. The durations of pyrexia (≥38.5°C) and other adverse clinical symptoms experienced by the Y10 group were significantly shorter than those of the LP93 group.